Endovascular Treatment of Visceral Artery Aneurysms and Pseudoaneurysms in 100 Patients: Covered Stenting vs Transcatheter Embolization. (October 2017) - Venturini, Massimo; Marra, Paolo; Colombo, Michele; Alparone, Marco; Agostini, Giulia; Bertoglio, Luca; Sallemi, Claudio; Salvioni, Marco; Gusmini, Simone; Balzano, Gianpaolo; Castellano, Renata; Aldrighetti, Luca; et al.
Purpose: To retrospectively report a large single-center experience of visceral artery aneurysms (VAAs) and pseudoaneurysms (VAPAs) treated with covered stenting (CS) as the first therapeutic option vs transcatheter embolization (TE).Methods: One hundred patients (mean age 59±14 years; 58 men) underwent 59 elective and 41 emergent endovascular procedures to treat 51 VAAs and 49 VAPAs. Seventy patients had TE and 30 received CS (27 Viabahn and 3 coronary stent grafts). Both TE and CS were performed in 10 cases.Results: Technical success was 96% (97% CS, 96% TE), and 30-day clinical success was 83% (87% CS, 81.4% TE). Four major complications occurred; 30-day mortality was 7%, mainly due to septic shock following pancreatic surgery. The midterm follow-up was 20.8 months in the total population and 32.8 months in the CS group. More than 6 months after CS all aneurysms remained excluded; stent patency was achieved in 88%. Twelve CS patients with >3 years' follow-up had maintained stent patency.Conclusion: In endovascular treatment of visceral aneurysms, covered stenting was feasible in 30%. CS showed a slightly better efficacy than TE and good midterm patency. The Viabahn covered stent seems to be suitable for endovascular repair of tortuous visceral arteries affected by true or false aneurysms.